Jenis-Jenis Paku Sarang (Asplenium): Aspleniaceae di Gunung Singgalang Sumatera Barat - Hari Fitrah; Ardinis Arbain; - Mildawati (Universitas Andalas, 2014)
Taxonomical study of Asplenium fern has been conducted in Mt. Singgalang, West Sumatra from April to July 2013. The purpose of this study was to identify the Asplenium species in the mountain and to describe their morphological characteristics. The sample were collected using survey and observation methods along habitual paths at Koto Baru, Tanah Datar and Balingka, Agam. The result of this study have found eleven species of Asplenium. Those spesies were A. affine, A. caudatum, A. glaucaphyllum, A. nidus, A. pellucidum, A. phylitids, A. polyodon, A. salignum, A. scortechinii, A. tenerum and A. unilateral. Those species belong to all five original groups of Asplenium based on morphological characteristics.Keywords: Asplenium, characteristics, mount Singgalang, species